The Moderating Effect of Institutional Ownership on the Relationship between Audit Committee Characteristics and Corporate Sustainability Disclosure among Listed Firms in East Africa Community Member States - Wahome, Emmanuel C. M.; Rono, Prof. Lucy; Yego, Dr. Jacob (International Journal of Scientific Research and Management (IJSRM), 2025)
This paper is investigating the moderation effect of institutional ownership on the relationship between audit committee characteristics and corporate sustainability disclosure. The study was formed on agency and stakeholder theories, using secondary data from 708 firm-year observations spanning 2012–2022. The findings indicated that audit committee characteristics (gender diversity, frequency of meetings, financial expertise, and size) significantly enhance CSD. Institutional ownership moderates these relationships positively, emphasizing on the impact of governance mechanisms on disclosures. The study recommends policy reforms to mandate diversity and expertise in audit committees, engagement with institutional investors, and regional collaboration to harmonize governance standards. This study has contributed to the growing literature on corporate governance and sustainability in emerging economies, highlighting institutional ownership as a pivotal factor in promoting transparency.